Exposure to Meconium-Stained Amniotic Fluid and Long-Term Neurological-Related Hospitalizations throughout Childhood - Matalon, Ron; Wainstock, Tamar; Walfisch, Asnat; Sheiner, Eyal (American Journal of Perinatology, 2020)
Objective This study aimed to investigate the possible impact of meconium-stained amniotic fluid (MSAF) on the occurrence of neurological-related hospitalizations throughout childhood and adolescence.Study Design In this population-based cohort analysis, all singleton deliveries occurring between 1991 and 2014 at the Soroka University Medical center were included and the long-term neurological-related hospitalizations were compared between children with and without MSAF during their delivery. A Kaplan-Meier survival analysis was constructed for the evaluation of cumulative hospitalization rate due to neurological morbidity over the 18 years of follow-up, and a Cox proportional hazards model was used to study the independent association between MSAF and childhood neurological morbidity while controlling for potential confounders.Results During the study period, 243,725 deliveries met the inclusion criteria; 35,897 of the cohort (15%) constituted the exposed group (MSAF), while the rest of the cohort (n = 207,828) constituted the unexposed group (no MSAF). A total of 7,543 hospitalizations due to neurological-related morbidity were documented with a rate of 3.2% (1,152) in children exposed to MSAF as compared with 3.1% (6,391) in the unexposed group (OR 1.1, 95% confidence interval 0.9–1.1, p = 0.149). The survival curve showed a comparable cumulative hospitalization rate in the MSAF-exposed group compared with the unexposed group (log rank p = 0.349). The Cox analysis, controlled for gestational diabetes and hypertension, gestational and maternal ages, demonstrated MSAF exposure not to be an independent risk factor for neurological-related hospitalizations during childhood (adjusted hazard ratio = 1.03, 0.96–1.09).Conclusion Fetal exposure to MSAF, at any gestational age, does not appear to be an independent risk factor for later neurological-related hospitalizations throughout childhood and adolescence.Key Points
Keywords: meconium-stained amniotic fluid; long-term outcome; neurological morbidity